Assessment of pathomorphological characteristics of the oral mucosa in patients with HBV, HCV and HIV - Vahe Azatyan; Lazar Yessayan; Anna Khachatryan; Anush Perikhanyan; Alvard Hovhannisyan; Melanya Shmavonyan; Hasmik Ghazinyan; Robert Gish; Gayane Melik-Andreasyan; Kristina Porksheyan (Journal of Infection in Developing Countries)
Introduction: Oral clinical manifestations in HBV HCV and HIV patients indicate a deterioration in general health status. The aim of the study was to assess pathomorphologic features of oral mucosa observed in patients with these diseases.